2018
DOI: 10.1001/jamanetworkopen.2018.5993
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Medicare Advantage Risk Adjustment Model for Measuring Veterans Affairs Hospital Performance

Abstract: This cohort study of administrative data from the Veterans Affairs Health Care System assesses the applicability of using the Medicare Advantage risk adjustment system version 21 for comparing Veterans Affairs hospitals with nonfederal hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…First, the VA population is different from the general population, and patients are more likely to be male, older, and have more comorbidities. 24 Although these differences would likely make this population more likely to suffer adverse outcomes associated with delays, it is unclear if other populations would have similar experiences with canceled surgical cases due to COVID-19. Furthermore, our analysis was limited to VA data and did not include referrals to or care from non-VA or community providers due to lag in claims data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the VA population is different from the general population, and patients are more likely to be male, older, and have more comorbidities. 24 Although these differences would likely make this population more likely to suffer adverse outcomes associated with delays, it is unclear if other populations would have similar experiences with canceled surgical cases due to COVID-19. Furthermore, our analysis was limited to VA data and did not include referrals to or care from non-VA or community providers due to lag in claims data.…”
Section: Discussionmentioning
confidence: 99%
“…First, the VA population is different from the general population, and patients are more likely to be male, older, and have more comorbidities. 24 Although these differences would likely make this population more likely to suffer…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, since risk adjustment models are developed on historical data, they tend to perpetuate inequality of past spending trends if no explicit adjustments are made to account for the endogeneity of spending. Prior work has investigated methods to develop fairer healthcare payment models through data manipulation and modeling changes [39,41,50], which can be pursued in future studies. Fourth, the SDH indicators used in this study are at the area-level which may lead to bias or ecological fallacy in the risk adjustment models.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that the inclusion of mental health variables in risk adjustment models for Veterans significantly improves model fit when predicting health care costs. 59 Fifth, we conducted analyses among the sub-set of individuals who self-identify as Veterans in the HRS. Finally, we used panel generalized estimating equations with a binomial distribution and log link for binary outcomes and a Gaussian distribution and identity link for continuous variables.…”
Section: Sensitivity Analysesmentioning
confidence: 99%